An investigation into the parameters affecting total harmonic distortion in low-voltage low-power class-D amplifiers - Tan, Meng Tong (2009)
We investigate the influence of two important practical design parameters on total harmonic distortion (THD) for the design of low-voltage (0.9–1.4 V) low-power analog Class-D amplifiers: the linearity of the carrier waveform and the impedance of the output stage. We show that the carrier nonlinearity results in THD and propose a novel mathematical analysis method to model the nonlinearity. We recommend a range of the parameter that describes the carrier nonlinearity and that results in a good compromise to the dynamic range of the pulsewidth modulator of the Class-D amplifier. We show that the impedance of the output stage has little effect on THD. We verify our analyses by means of MATLAB and HSPICE computer simulations, and on the basis